Pengaruh Temperatur dan Zeolit terhadap Volume dan Nilai Kalor Tar Pada Proses Pirolisis Serbuk Batang Bambu - Anggunio, Cornelius; Hermawan, Dadang; Suwandono, Purbo (PROTON, 2024)
Waste is a problem in Indonesia, both organic and non-organic waste. Bambo powder is an organic waste that can still be utilized to produce energy using the pyrolysis method. The research aims to utilize bambo waste to produce tar using pyrolysis process with temperature variation and with the addition of zeolite. The research method uses 200 g of bamboo powder with a moisture content of less than 2% and 40 g of zeolite and a heating process with a duration of 3 hours. The pyrolysis gas was condensed to obtain tar. The research produced the most tar products at a temperature of 550 ⁰C as much as 57 milli and 72 milli in the addition of zeolite. In the pure pyrolysis process, the highest calorific value was obtained at a temperature of 450 ⁰C amounting to 149.27 (cal/g) at the addition of zeolite, the highest calorific value was obtained at a temperature of 550 ⁰C amounting to 248.29 (cal/g). This shows that adding zeolite to the pyrolysis process can increase the amount of tar when compared to pure pyrolysis both in quality and quantity.